Fabrication of binary metal doped CuO nanocatalyst and their application for the industrial effluents treatment. Issue 5 (1st March 2021) - ur Rehman, Atta; Aadil, Muhammad; Zulfiqar, Sonia; Agboola, Philips O.; Shakir, Imran; Aly Aboud, Mohamed F.; Haider, Sajjad; Warsi, Muhammad Farooq
Abstract: Herein, we fabricated the binary transition metal (Ce & Zn) doped CuO nanocatalyst via a single step facile co-precipitation technique by using liquid ammonia as a pH regulator and precipitating agent. The structural, morphological, and compositional studies of the fabricated samples were completed via X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), and EDX techniques, respectively. The impact of binary metal-doped CuO nanocatalyst on the optical band-gap was examined via the UV-Visible spectroscopic technique. The photocatalytic aptitude of the fabricated pristine and binary metal-doped CuO nanocatalyst was examined against the 5-ppm aqueous solution of MB dye. The obtained results revealed that the doped sample removes 81.64% MB dye, via adsorption (32.65%) and degradation (48.99%) processes, while in comparison the pristine CuO sample removes just 38.77%. The superior adsorption and degradation aptitude of the binary metal-doped sample can be ascribed to its higher surface area and tuned band-gap, respectively. Moreover, the kinetic study of the degradation process also displayed that the doped sample degrades the MB dye with a higher value of the rate constant (0.0137 min −1 ) than that of pristine CuO photocatalyst (0.0049 min −1 ). The tuned band-gap and nanoarchitecture morphology of the doped CuO not only facilitate the excitation process but also assist in the transportation of the photo-induced species towards the surface of the photocatalyst. The observed superior photocatalytic activity of the binary metal-doped CuO photocatalyst showed its exceptional aptitude for the treatment of toxic industrial effluents. Graphical abstract: Image 1